Niacin protects against abdominal aortic aneurysm formation via GPR109A independent mechanisms: role of NAD+/nicotinamide. Issue 14 (9th November 2019) - Horimatsu, Tetsuo; Blomkalns, Andra L; Ogbi, Mourad; Moses, Mary; Kim, David; Patel, Sagar; Gilreath, Nicole; Reid, Lauren; Benson, Tyler W; Pye, Jonathan; Ahmadieh, Samah; Thompson, Allie; et al.
Abstract: Aims: Chronic adventitial and medial infiltration of immune cells play an important role in the pathogenesis of abdominal aortic aneurysms (AAAs). Nicotinic acid (niacin) was shown to inhibit atherosclerosis by activating the anti-inflammatory G protein-coupled receptor GPR109A [also known as hydroxycarboxylic acid receptor 2 (HCA2)] expressed on immune cells, blunting immune activation and adventitial inflammatory cell infiltration. Here, we investigated the role of niacin and GPR109A in regulating AAA formation. Methods and results: Mice were supplemented with niacin or nicotinamide, and AAA was induced by angiotensin II (AngII) infusion or calcium chloride (CaCl2 ) application. Niacin markedly reduced AAA formation in both AngII and CaCl2 models, diminishing adventitial immune cell infiltration, concomitant inflammatory responses, and matrix degradation. Unexpectedly, GPR109A gene deletion did not abrogate the protective effects of niacin against AAA formation, suggesting GPR109A-independent mechanisms. Interestingly, nicotinamide, which does not activate GPR109A, also inhibited AAA formation and phenocopied the effects of niacin. Mechanistically, both niacin and nicotinamide supplementation increased nicotinamide adenine dinucleotide (NAD + ) levels and NAD + -dependent Sirt1 activity, which were reduced in AAA tissues. Furthermore, pharmacological inhibition of Sirt1 abrogated the protective effect of nicotinamide against AAA formation. Conclusion: Niacin protects against AAA formation independent of GPR109A, most likely by serving as an NAD + precursor. Supplementation of NAD + using nicotinamide-related biomolecules may represent an effective and well-tolerated approach to preventing or treating AAA.